Effects of Teacher Professional Development on Implementation of Competency-Based Curriculum in Junior Schools in North Imenti Sub-County, Meru County - wegoki, christabel; Njati, Ibuath C.; Njagi, Kageni (Meru Universty of Science and Technology International Conference (MUSTIC), 2025)
Kenya is experiencing a gradual transition from a content-focused education (8-4-4) to a competency-based curriculum (2-6-3-3-3). However, there has been insufficient pedagogical preparedness among teachers and a lack of comprehensive content knowledge for competency-based curricula. This research focused on examining the effects of teacher professional development on the implementation of the competency-based curriculum in junior secondary schools in North Imenti, Meru County. The study's objectives were to evaluate how enhancements in professional development, particularly in pedagogical skills, could facilitate the successful implementation of CBC. The literature review synthesizes existing studies on competency-based education, with a focus on the importance of aligning teacher professional development with curriculum demands. The study used a descriptive survey design. The target population comprised 26 junior schools in North Imenti Sub-County, Meru County. The respondents were 2 sub-county education directors, 26 head teachers, and 70 junior school teachers. Through stratified sampling, the sample size was 31 respondents, 8 head teachers, 21 teachers, and 2 sub-county directors of education. The data was collected using questionnaires, interview schedules, and observation checklists. The findings indicated that most of the junior school teachers (95%) had undergone professional development in the implementation of a Competency-Based Curriculum. The study concluded that Teacher Professional Development is important for equipping teachers with the necessary skills and knowledge for effective implementation of a Competency-Based Curriculum. The study recommended the development of continuous, competency-focused professional development initiatives that address these critical areas of instructional methodologies.